2008
DOI: 10.1002/hyp.6945
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure effects on floods in the Mekong River Delta in Vietnam

Abstract: The Mekong River Delta (MRD) is one of two primary rice-growing areas in Vietnam. Flooding in the Mekong River is a recurrent event and is not only one of the most destructive natural disasters but also a natural resource in this area. The cultivated surface soil layer in the Mekong Delta has a thickness of only about 50 cm, and is heavily polluted by acidic water infiltrating from deeper soil layers during the dry season. The annual floods carry fertile silt to farmland and fresh water to wash away the acidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 12 publications
3
38
1
Order By: Relevance
“…Hoa et al (2007) predicted that ''The future flood control works planned to be completed by 2010 will cause an increase in runoff peaks and prolong the duration of the flood recession. '' In general, the present study confirms that three sea level rise scenarios will lead to an increase of the water level in the rainy season and to an expanded salinity intrusion in the dry season both at spatial and temporal scales in the Mekong Delta, Vietnam, thus increasing the vulnerability of the delta area to climate changes (Wassmann et al 2004;Khang et al 2008;Hoa et al 2008). Syvitski et al (2009) presented an assessment of 33 densely populated and heavily farmed deltas globally and estimated the delta areas vulnerable to flooding could increase by 50 % by sea level rise in the twenty-first century.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Hoa et al (2007) predicted that ''The future flood control works planned to be completed by 2010 will cause an increase in runoff peaks and prolong the duration of the flood recession. '' In general, the present study confirms that three sea level rise scenarios will lead to an increase of the water level in the rainy season and to an expanded salinity intrusion in the dry season both at spatial and temporal scales in the Mekong Delta, Vietnam, thus increasing the vulnerability of the delta area to climate changes (Wassmann et al 2004;Khang et al 2008;Hoa et al 2008). Syvitski et al (2009) presented an assessment of 33 densely populated and heavily farmed deltas globally and estimated the delta areas vulnerable to flooding could increase by 50 % by sea level rise in the twenty-first century.…”
Section: Discussionsupporting
confidence: 83%
“…We assessed the impacts of water level and salinity intrusion along the Tien and Hau branches of the Mekong river in time and space by applying model-based scenarios for sea level rise and reduced river flow (e.g., Alcamo et al 1998;Wassmann et al 2004;Hoa et al 2007Hoa et al , 2008Khang et al 2008). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…South of Vam Nao, the water volumes of the two rivers become more balanced, owing to interconnecting tributaries. Due to the delta's flat, low-lying topography (its average elevation is just 0.8 m above mean sea level) and the impact of tidal regimes (Hung, 2012), the annual floods inundate 1.2 to 1.9 million ha of the delta (Hoa et al, 2008; Kingdom of the Netherlands and the Socialist Republic of Vietnam, 2013). In a severe flood season, water depths reach up to 3 m, affecting the lives of more than 2 million residents.…”
Section: Study Areamentioning
confidence: 99%
“…Hoa et al (2008) used the HydroGIS hydrodynamic model to evaluate the effects of the infrastructural changes from 1996 to 2004 on floodwater levels and flood protection efficacy. They concluded that infrastructure works, such as dredging canals, raising embankments, and upgrading roads, likely mitigated the overall extent of flooding but increased flood depth by 20 to 30 cm in some regions near and between embankment systems.…”
Section: Introductionmentioning
confidence: 99%